Identification of an intrahepatic transcriptional signature associated with self‐limiting infection in the woodchuck model of hepatitis B12. Issue 1 (7th January 2013) - Fletcher, Simon P.; Chin, Daniel J.; Cheng, Donavan T.; Ravindran, Palanikumar; Bitter, Hans; Gruenbaum, Lore; Cote, Paul J.; Ma, Han; Klumpp, Klaus; Menne, Stephan
Abstract The woodchuck model of hepatitis B virus (HBV) infection displays many characteristics of human infection and has particular value for characterizing the host immune responses during the development of chronic infection. Using the newly developed custom woodchuck microarray platform, we compared the intrahepatic transcriptional profiles of neonatal woodchucks with self‐limiting woodchuck hepatitis virus (WHV) infection to those woodchucks progressing to persistent WHV infection. This revealed that WHV does not induce significant intrahepatic gene expression changes during the early‐acute stage of infection (8 weeks), suggesting it is a stealth virus. At the mid‐acute phase of infection (14 weeks), resolution was associated with induction of a prominent cytotoxic T‐cell signature. Strikingly, this was accompanied by high‐level expression of PD‐1 and various other inhibitory T‐cell receptors, which likely act to minimize liver damage by cytotoxic T cells during viral clearance. In contrast to the expression of perforin and other cytotoxic effector genes, the interferon‐γ (IFN‐γ) signaling response in the mid‐acute phase was comparable to that in chronically infected adult animals. The absence of a strong IFN‐α/β transcriptional response indicated that type I IFN is not a critical mediator of self‐limiting infection. Nevertheless, a number of antiviral genes, including viperin, were differentially expressed during resolving infection, suggesting that a subset of IFN‐stimulated genes (ISG) may play a role in the control of WHV replication. Conclusion: We identified new immune pathways associated with the clearance of hepadnavirus infection revealing novel molecular targets with potential for the therapeutic treatment of chronic hepatitis B. (HEPATOLOGY 2013)